Federal offices of the inspector general: thriving on chaos? - Newcomer, Kathryn; Grob, George (2004)
Rapid change in responsibilities, requirements, and human resource demands has been the constant for federal Offices of the Inspector General over the past decade. They have been drawn into work on the management challenges facing their agencies, new requirements levied by the Chief Financial Officers Act and the Government Performance and Results Act, and crisis management efforts imposed by recent homeland security threats. This study replicates previous surveys of the Office of the Inspector General community undertaken in 1992 and 1996 to assess how it is meeting current challenges and has changed in its roles and responsibilities over the past decade. The study found the Inspector General community evolving and stretching to meet new demands while retaining core functions. It is expanding its repertoire of analytical services, working closely with agency management to address management challenges, and confronting new human capital needs, especially in the field of information technology. - Reproduced.
Keywords: Accountability; Civil service